Three new species of Aulonemia (Poaceae: Bambusoideae) from the Brazilian Atlantic rainforest - Viana, Pedro Lage; Filgueiras, Tarciso S. (Phytotaxa, 2014)
Three new Brazilian species of Aulonemia, a Neotropical woody bamboo genus, are described and illustrated: Aulonemia cincta, with its distinctive corky girdles; Aulonemia prolifera, characterized, among other Brazilian congeners, by its fimbriate leaf sheaths; and Aulonemia soderstromii, with its conspicuous cluster of spreading fimbriae. These new species all propagate by amphipodial rhizomes, an unusual feature shared with the Brazilian species A. aristulata, with which they are morphologically compared. Comments about habitat, distribution, phenology, and conservation status for each species are provided, as well as photographs taken in the wild.